The mechanistic role of active site residues in non-stereo Haloacid Dehalogenase E (DehE) - Zainal Abidin, Muhammad Hasanuddin; Abd Halim, Khairul Bariyyah; Huyop, Fahrul Zaman; Tengku Abdul Hamid, Tengku Haziyamin; Abdul Wahab, Roswanira; Abdul Hamid, Azzmer Azzar (2019)
Dehalogenase E (DehE) is a non-stereospecific enzyme produced by the soil bacterium, Rhizobium sp. RC1. Till now, the catalytic mechanism of DehE remains unclear although several literature concerning the structure and function of this enzyme are available. Since DehE is nonstereospecific, the enzyme was hypothesized to follow a ‘direct attack mechanism’ for the catalytic breakdown of haloacid. For a molecular insight, the DehE modelled structure was docked in silico with the substrate 2-chloropropionic acid (2CP) in the active site. The ideal position of DehE residues to allow a direct attack mechanism was then assessed via molecular dynamics (MD) simulation which revealed that after 50 ns, the essential catalytic water was hydrogen bonded consistently within a distance of ~2.0 Å with the ‘water-bearer’, Asn114. The same water molecule was also closely sited to the catalytic Asp189 at an average distance of ~2.0 Å, thus clearly demonstrating the inevitability of the initial step of proton abstraction. Activation of water was crucial to promote its direct attack on the α-carbon of 2CP and the impending release of halide ion. Finally, the water molecule was seen to favourably orient towards the α-carbon of 2CP as mirrored by formation of stable enzyme-substrate orientations throughout the simulation. Our findings therefore, substantiate the DehE catalyzing the degradation of haloacid via a ‘direct attack mechanism’. This work would provide a fundamental knowledge for protein engineering and solvent stability studies specifically on the haloacid dehalogenase enzymes.